Tetraploidization events by chromosome doubling of nucellar cells are frequent in apomictic citrus and are dependent on genotype and environment - Aleza, Pablo; Froelicher, Yann; Schwarz, Sergio; Agustí, Manuel; Hernández, María; Juárez, José; Luro, Francois; Morillon, Raphael; Navarro, Luis; Ollitrault, Patrick (2017)
† Background and Aims Polyploidy is a major component of plant evolution. The citrus gene pool is essentially diploid but tetraploid plants are frequently encountered in seedlings of diploid apomictic genotypes. The main objectives of the present study were to establish the origin of these tetraploid plants and to ascertain the importance of genotypic and environmental factors on tetraploid formation. † Methods Tetraploid seedlings from 30 diploid apomictic genotypes were selected by flow cytometry and genotyped with 24 single sequence repeat (SSR) markers to analyse their genetic origin. Embryo rescue was used to grow all embryos contained in polyembryonic seeds of ‘Tardivo di Ciaculli’ mandarin, followed by characterization of the plantlets obtained by flow cytometry and SSR markers to accurately establish the rate of tetraploidization events and their potential tissue location. Inter-annual variations in tetraploid seedling rates were analysed for seven genotypes. Variation in tetraploid plantlet rates was analysed between different seedlings of the same genotype (‘Carrizo’ citrange; Citrus sinensis × Poncirus trifoliata) from seeds collected in different tropical, subtropical and Mediterranean countries. †Key Results Tetraploid plants were obtained for all the studied diploid genotypes, except for four mandarins. All tetraploid plants were identical to their diploid maternal line for SSR markers and were not cytochimeric. Significant genotypic and environmental effects were observed, as well as negative correlation between mean temperature during the flowering period and tetraploidy seedling rates. The higher frequencies (20 %) of tetraploids were observed for citranges cultivated in the Mediterranean area. †Conclusions Tetraploidization by chromosome doubling of nucellar cells are frequent events in apomictic citrus, and are affected by both genotypic and environmental factors. Colder conditions in marginal climatic areas appear to favour the expression of tetraploidization. Tetraploid genotypes arising from chromosome doubling of apomictic citrus are extensively being used as parents in breeding programmes to develop seedless triploid cultivars and have potential direct use as new rootstocks.